Eugene and Eloise Armstrong letter to Thomas H. Kent regarding bird sightings near Booneville, Iowa, spring 1984 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1984)
Eugene and Eloise Armstrong letter to Thomas H. Kent regarding bird sightings near Booneville, Iowa, spring 1984. They saw a Cattle Egret, Upland Sandpipers, and a Western Kingbird south of Booneville. At the Ankeny Ponds, they saw Ruddy Turnstones and Buff-breasted Sandpipers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed/flatbed